Analisis Peran Media Sosial dalam Meningkatnya Kecanduan Internet di Kalangan Remaja: Studi Kasus Patologi Sosial - Zakariya, Akhmad Sahlan; Khodijah, Khodijah (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p21, 2025)
Social media plays a crucial role in the lives of today's adolescents. Its function goes beyond facilitating interaction and communication; it also has significant social and psychological impacts. In this study, the employed methods include literature review and content analysis from various relevant sources. The research findings reveal that the role of social media is highly significant in increasing internet usage among adolescents, but it also carries undeniable negative impacts on their well-being. One particularly relevant concept is the "Fear of Missing Out" (FoMO), which can influence the behavior and social interactions of adolescents on social media platforms. The necessity for wise management of social media use and the implementation of appropriate educational approaches are becoming increasingly important as preventive measures to address the negative effects of social media addiction among adolescents. Therefore, efforts that support the understanding and awareness of adolescents regarding social media usage need to be implemented. This is crucial to enable them to adopt a prudent approach when interacting in the virtual world.